Penerapan Autonomous Vehicle Behavior Pada Permainan Simulasi Ujian Berkendara 3D Menggunakan Metode Steering Behavior - Rosikhan Maulana Yusuf; Eriq Muhammad Adams Jonemaro; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Driving simulation is one means to improve one's ability to drive. The design of 3D driving simulations that have been created can provide control and visual support for driving learning. However, in the real-world riders are not just dealing with traffic signs. Players also require real-world driving learning in addition to other cars that move like in the real world. So it takes an automatic agent that acts as a car. The solution for this automated agent is to use Autonomous Vehicle which uses the Steering Behavior method as the base. At design stage, the requirement in making Steering Behavior is arranged in Car Controller design, Steering Behavior design and Waypoint design. Then the program is implemented using Unity3D with C# programming language. At the time of testing White Box, it can be concluded that the unit module program already meets the functional needs. In the test of accuracy and precision, it can be concluded that offset accuracy is 97.9% and offset precision is 0.166427546 meter. The magnitude error accuracy is 68.3% and magnitude error precision is 1.605146908 m/s. In performance testing, it can be concluded that the best performance of Autonomous Vehicle can handle is when executing agents simultaneously with no more than 180 agents.